Cladribine tablets added to IFN-β in active relapsing MS: The ONWARD study. Issue 5 (September 2018) - Montalban, Xavier; Leist, Thomas P.; Cohen, Bruce A.; Moses, Harold; Campbell, Jackie; Hicking, Christine; Dangond, Fernando; Comi, Giancarlo; Gallo, Paolo; Pozzilli, Carlo; Gasperini, Claudio; Morra, Vincenzo Brescia; et al.
Abstract : Objective: To evaluate the safety and efficacy of cladribine tablets in patients still experiencing active relapsing MS despite interferon (IFN)-β treatment. Methods: A 96-week phase II study, randomizing patients treated with IFN-β to cladribine tablets 3.5 mg/kg/IFN-β or placebo/IFN-β. Patients were to receive cladribine tablets 3.5 mg/kg/IFN-β or placebo/IFN-β in a 2:1 ratio (n = 172) with safety and exploratory efficacy outcomes being assessed. Results: Adverse events (AEs) and serious AEs were similar across treatment groups, except lymphopenia. Fifty of 124 (40.3%) cladribine/IFN-β recipients vs 0% of placebo/IFN-β recipients reported lymphopenia as an AE, with grade 3/4 lymphopenia (laboratory lymphocyte count < 500 cells/mm 3 ) experienced by 79/124 (63.7%) vs 1 (2.1%), respectively. Patients treated with cladribine tablets 3.5 mg/kg/IFN-β were 63% less likely to have a qualifying relapse than placebo/IFN-β recipients, and cladribine tablets 3.5 mg/kg/IFN-β reduced most MRI measures of disease activity. Conclusions: In patients with active relapsing MS despite IFN-β treatment, cladribine tablets 3.5 mg/kg/IFN-β reduced relapses and MRI lesion activity over 96 weeks compared with placebo/IFN-β but led to an increased incidence of lymphopenia. Classification of evidence: This study provides Class I evidence that for patients with active relapsing MS despite IFN-β treatment, cladribine tablets added to IFN-β reduced relapses and MRI lesion activity over 96 weeks and increased the incidence of lymphopenia. Clinical trial registration: NCT00436826.